2018
DOI: 10.1111/ajt.14601
|View full text |Cite
|
Sign up to set email alerts
|

Early barriers to neonatal porcine islet engraftment in a dual transplant model

Abstract: Porcine islet xenografts have the potential to provide an inexhaustible source of islets for β cell replacement. Proof-of-concept has been established in nonhuman primates. However, significant barriers to xenoislet transplantation remain, including the poorly understood instant blood-mediated inflammatory reaction and a thorough understanding of early xeno-specific immune responses. A paucity of data exist comparing xeno-specific immune responses with alloislet (AI) responses in primates. We recently develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Like the two early studies in this dual transplant series, we observed a nonspecific milieu of antibody, complement, and coagulation immediately following intraportal infusion of NPIs . At 1‐hour, human CD46 expression on NPIs did not provide any perceived advantage at this stage.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…Like the two early studies in this dual transplant series, we observed a nonspecific milieu of antibody, complement, and coagulation immediately following intraportal infusion of NPIs . At 1‐hour, human CD46 expression on NPIs did not provide any perceived advantage at this stage.…”
Section: Discussionsupporting
confidence: 62%
“…That the effects seen in this series of experiments relate more to cellular accumulation, it suggests that a reduction in the chemotactic effects of non‐bound complement breakdown products may be the most relevant in this setting. Interestingly, we have previously reported on increased staining of C4d in allogeneic islets compared to NPIs 7 days post‐infusion . Although C3d and C4d are widely used as marker for complement activation, they have not been verified in the setting of IBMIR .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations